2020
DOI: 10.3389/fsufs.2020.00144
|View full text |Cite
|
Sign up to set email alerts
|

Consumers' Willingness to Consume Insect-Based Protein Depends on Descriptive Social Norms

Abstract: Eating of insects has been discussed as a more sustainable source of animal protein, but consumer research about uptake behavior of Western consumers is still scarce. Based on previous psychological research highlighting the role of social norms, the present research shows that even subtle cues about descriptive social norms affect Westerners' willingness to eat unprocessed insects. In a series of four studies, we demonstrate that adherence to descriptive social norms underlies eating intention and behavior. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 36 publications
0
17
1
Order By: Relevance
“…Previous reviews have indicated that the concept of eating insects would likely be more appealing to younger people than older people ( 4 , 21 , 22 ). In contrast, the majority of studies (61.1%) in our review concluded that there was no link between age and Westerners' acceptance of edible insects ( 39 , 41 , 42 , 48 , 51 , 55 , 56 , 58 , 61 , 62 , 64 , 66 , 72 74 , 86 , 104 106 , 108 , 109 , 117 ). However, 36.1% of all studies that evaluated the effect of age on consumers' acceptance observed a negative effect of age ( 2 , 64 , 65 , 67 , 71 , 76 , 77 , 87 , 92 , 93 , 97 , 99 , 115 ), which means that younger people had a higher acceptance of insect-based foods than older people, while two studies (5.6%) identified a positive connection ( 49 , 107 ).…”
Section: Resultscontrasting
confidence: 64%
See 2 more Smart Citations
“…Previous reviews have indicated that the concept of eating insects would likely be more appealing to younger people than older people ( 4 , 21 , 22 ). In contrast, the majority of studies (61.1%) in our review concluded that there was no link between age and Westerners' acceptance of edible insects ( 39 , 41 , 42 , 48 , 51 , 55 , 56 , 58 , 61 , 62 , 64 , 66 , 72 74 , 86 , 104 106 , 108 , 109 , 117 ). However, 36.1% of all studies that evaluated the effect of age on consumers' acceptance observed a negative effect of age ( 2 , 64 , 65 , 67 , 71 , 76 , 77 , 87 , 92 , 93 , 97 , 99 , 115 ), which means that younger people had a higher acceptance of insect-based foods than older people, while two studies (5.6%) identified a positive connection ( 49 , 107 ).…”
Section: Resultscontrasting
confidence: 64%
“…The most frequently investigated factor affecting the acceptance of insects as food is gender, a variable known to have an effect on dietary habits ( 37 , 110 ). Of the 119 studies reviewed, 52 examined gender ( 2 , 36 , 37 , 39 , 41 , 42 , 44 , 49 , 51 , 55 , 56 , 58 , 61 , 62 , 64 – 67 , 69 , 71 74 , 76 , 77 , 83 , 84 , 86 , 87 , 92 94 , 96 , 97 , 99 101 , 104 109 , 111 117 ). Of those 52 studies, 71.2% identified masculinity as a positive influence on acceptance of insects as food ( 2 , 36 , 41 , 44 , 51 , 55 , 58 , 61 , 62 , 65 – 67 , 69 , 71 , 76 , 77 , 83 , 84 , 86 , 87 , 92 94 , 96 , 97 , 99 101 , 104 , 105 , 112 , 114 ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Past research suggests U.S. consumers often are averse to consuming insects primarily due to (a) a lack of exposure in context as a food source, (b) a lack of social acceptance, and (c) a lack of consumer access (Looy et al, 2014;Caparros Megido et al, 2016;Menozzi et al, 2017). Distribution in universities directly confronts these barriers as it allows for marketing (1) with continual exposure alongside more familiar foods (Gumussoy et al, 2021), (2) among environmentally conscious peers thereby encouraging normative influence (Berger and Wyss, 2020;Russell and Knott, 2021), and (3) without typical barriers to consumer purchasing such as price or preparation (Barska, 2014;Menozzi et al, 2017).…”
Section: Marketing and Consumption: University Foodservice And Flexit...mentioning
confidence: 99%
“…Social networks are seen as affecting intentions by means of descriptive social influence (what others do), [72][73][74] and the relative influence that the behaviour of others has on the agent. In Giddens' words, "the reflexive monitoring of activity is a chronic feature of everyday action and involves the conduct not just of the individual but also of others" [53].…”
Section: Theoretical Backgroundmentioning
confidence: 99%